2015
DOI: 10.2147/clep.s82389
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis case finding in first-degree relative contacts not living with index tuberculosis cases in Kampala, Uganda

Abstract: PurposeTo assess the prevalence of pulmonary tuberculosis among first-degree relative (FDR) contacts not living with tuberculosis (TB) cases.MethodsA cross-sectional analysis of household contacts living with an index TB case and FDR contacts living outside of households in Kampala, Uganda, is presented.ResultsA total of 177 contacts (52 FDRs and 125 index household contacts) of 31 TB cases were examined. Compared with index household contacts, FDR contacts were older, more likely to be TB symptomatic (50% vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…A total of 79 Ugandans (Supplementary Tables 1 and 2) who were recruited from the Kawempe Community Health Study were included in this analysis 9,52 . Index individuals with pulmonary TB were identified by culture for confirmed pulmonary TB at the Uganda National Referral Tuberculosis Treatment Center at Upper Mulago Hospital in Kampala, Uganda, between 2002 and 2012.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 79 Ugandans (Supplementary Tables 1 and 2) who were recruited from the Kawempe Community Health Study were included in this analysis 9,52 . Index individuals with pulmonary TB were identified by culture for confirmed pulmonary TB at the Uganda National Referral Tuberculosis Treatment Center at Upper Mulago Hospital in Kampala, Uganda, between 2002 and 2012.…”
Section: Methodsmentioning
confidence: 99%
“…The yield was higher at 1.4% among the neighbor contacts. Cheng et al (2015) from Uganda showed that first degree relatives’ contacts were more likely to be symptomatic for TB [ 18 ]. It was also shown by Lienherdt et al (2003) in Gambia that development of TB cases increased with first degree relatives compared with more distant and non-genetically related households [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, earlier contact investigation studies in Ethiopia used only household contacts of SS+ index cases [ 11 , 14 ]. While there is some evidence that TB among close contacts of SS-[ 15 17 ] and in contacts other than households [ 18 , 19 ] is high, this has not been demonstrated in routine program settings.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, newly diagnosed tuberculosis patients were identified at the Uganda National Referral Tuberculosis Treatment Center at Upper Mulago Hospital in Kampala, Uganda. The index cases were enrolled if they had culture confirmed pulmonary tuberculosis and had at least one household contact living with them[ 19 ]. Between 2002 and 2012, 2585 household contacts were enrolled and followed prospectively for up to two years for development of tuberculosis disease or diagnosis of latent tuberculosis infection by serial TSTs at 0, 3, 6, 12, 18,and 24 months.…”
Section: Methodsmentioning
confidence: 99%